Free radicals, nitric oxide, and inflammation : molecular, biochemical, and clinical aspects - Özben, Tomris; Skulachev, V. P. (Vladimir Petrovich); Tomasi, Aldo (NATO science series. Life and behavioural sciences, 2003)
Free radicals, and the very special free radical nitric oxide, are playing a relevant role in the pathogenesis of inflammation. This work introduces the general knowledge necessary to understand the inflammatory process and the role played by free radical and oxidative stress.